A COMPONENT ANALYSIS OF SCHEDULE THINNING DURING FUNCTIONAL COMMUNICATION TRAINING. Issue 1 (1st April 2013) - Betz, Alison M.; Fisher, Wayne W.; Roane, Henry S.; Mintz, Joslyn C.; Owen, Todd M.
Abstract One limitation of functional communication training (FCT) is that individuals may request reinforcement via the functional communication response (FCR) at exceedingly high rates. Multiple schedules with alternating periods of reinforcement and extinction of the FCR combined with gradually lengthening the extinction‐component interval can effectively address this limitation. However, the extent to which each of these components contributes to the effectiveness of the overall approach remains uncertain. In the current investigation, we evaluated the first component by comparing rates of the FCR and problem behavior under mixed and multiple schedules and evaluated the second component by rapidly switching from dense mixed and multiple schedules to lean multiple schedules without gradually thinning the density of reinforcement. Results indicated that multiple schedules decreased the overall rate of reinforcement for the FCR and maintained the strength of the FCR and low rates of problem behavior without gradually thinning the reinforcement schedule.